Morphological Characteristics of Changes in the Duodenal Wall Within 14-56 Days of the Development of Streptozotocin-Induced Experimental Diabetes Mellitus - Ihor Bilinskyi (Galician Medical Journal, 2020)
The objective of the research was to determine the morphological features of the duodenal wall of animals within 14-56 days of developing streptozotocin-induced diabetes mellitus using light optical microscopy.